Difficulties in the teaching of calculus I in distance engineering courses – Study and comparison with universities of face-to-face teaching - Mansur , Ana Mendonça; Moraes , Jessica Bueno de (Seven Editora, 2023)
The offer of distance learning courses and blended learning has gained space in the academic scenario year after year. The method uses technology and the facilities provided by it become allies in the learning process. Factors such as time, place and age group are no longer an obstacle for those who want to improve the curriculum. In engineering courses, in particular, performance in common axis disciplines such as Calculus remains a major difficulty on the part of students. The study shows possible causes and association with students in both teaching modalities. It should be noted that the difficulty of entering a higher education institution, such as the entrance exam, becomes a water divider in terms of the educational basis obtained in secondary and elementary education. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-057